Pick-up points optimization for a demand-responsive school bus service based on walking distance and demand points - Korompay, M.; Földes, D. (Харківський національний автомобільно-дорожній університет, 2024)
This paper presents a pick-up point optimizing method for demand-responsive school bus service. In the case of a school bus service, minimizing the walking distance is especially important in order to reduce the traffic safety and security risk of vulnerable users (aka students). The method developed is based on a demand-sensitive approach, where demand points are known. The method focuses on a clustering procedure that iterates demand points into units based on the acceptable walking distance. Pick-up points can be explicitly assigned to demand point units. A case study in Szentendre, Hungary, found that the allocation method significantly reduces walking distances compared to conventional transport systems, while the low number of pick-up points may ensure service efficiency.
Keywords: demand-responsive school bus; pick-up point; walking distance; clustering procedure; optimization algorithm; 656.1